2014 IEEE International Conference on Communications (ICC) 2014
DOI: 10.1109/icc.2014.6883501
|View full text |Cite
|
Sign up to set email alerts
|

A Differentiated Queueing Service based admission control policy for wireless multimedia

Abstract: Quality of Service (QoS) provisioning for wireless multimedia applications has attracted increasing research attentions. Due to limited bandwidth of time-varying wireless links and various QoS requirements of bursty multimedia applications, an effective call admission control (CAC) policy that efficiently utilizes the bandwidth is desired. We have proposed a Differentiated Queueing Service (DQS) to support per-packet differentiated services for admitted traffic, which has been illustrated feasibility for mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…To ensure the service quality of security situation information under the constraints of delay limitations and network resources [62], the research group designed a solution to schedule security situation information according to the urgency of data packet delay [63], to control the data flow into the system according to the capacity of the link, and to design a fast queueing method for data packets according to the queue leader [64]. For the data packet timeout and energy consumption problems caused by the dynamic nature of the wireless environment, the research group demonstrated the feasibility of actively dropping time-out data packets from both theoretical analysis and simulation validation [65].…”
Section: Work Of the Research Group On The Data Center Networkmentioning
confidence: 99%
“…To ensure the service quality of security situation information under the constraints of delay limitations and network resources [62], the research group designed a solution to schedule security situation information according to the urgency of data packet delay [63], to control the data flow into the system according to the capacity of the link, and to design a fast queueing method for data packets according to the queue leader [64]. For the data packet timeout and energy consumption problems caused by the dynamic nature of the wireless environment, the research group demonstrated the feasibility of actively dropping time-out data packets from both theoretical analysis and simulation validation [65].…”
Section: Work Of the Research Group On The Data Center Networkmentioning
confidence: 99%
“…The MDP model has been widely used in various applications in different communication networks such as the solutions described in previous studies . A dynamic‐preemption call admission control scheme has been proposed in a previous study to decide whether to preempt the existing requests based on the optimal policy derived from a MDP model.…”
Section: Introductionmentioning
confidence: 99%